THE INFLUENCE OF FAMILY SUPPORT AND SELF-ADJUSTMENT ON MOTIVATION TO RECOVER IN PRISONERS OF NARCOTICS CASES IN CLASS IIA PURWOKERTO CORRECTIONAL INSTITUTION - Pratidina, Adhi Gineung; Anwar , Umar (Jurnal Kajian Pendidikan dan Psikologi, 2024)
This study aims to analyze the influence of family support and self-adjustment on the motivation to recover among narcotics prisoners at the Class IIA Correctional Facility in Purwokerto. Family support plays a role in providing emotional and material encouragement that increases the prisoners' hope, while self-adjustment within the prison environment helps them cope with existing pressures, thereby enhancing their motivation to participate in rehabilitation programs. This research uses a quantitative method with a survey approach, collecting data through questionnaires distributed to 100 prisoners. The data analysis technique employed is multiple regression to determine the influence of each independent variable on recovery motivation. The analysis results show that family support and self-adjustment significantly influence prisoners' motivation to recover, with family support having a greater impact than self-adjustment. Emotional support from family makes prisoners feel valued and optimistic, while self-adjustment enables them to better face the challenges within the prison environment. Based on these findings, it is recommended that rehabilitation programs in correctional facilities involve the prisoners' families more and enhance programs that support prisoners' adjustment to the prison environment. In conclusion, family support and self-adjustment are important factors contributing to the motivation of prisoners to recover from narcotics addiction.